2020
DOI: 10.18632/aging.103090
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 is regulated by miR-135a and involved in DNA damage repair during mouse cellular reprogramming

Abstract: Sirt1 facilitates the reprogramming of mouse somatic cells into induced pluripotent stem cells (iPSCs). It is regulated by micro-RNA and reported to be a target of miR-135a. However, their relationship and roles on cellular reprogramming remain unknown. In this study, we found negative correlations between miR-135a and Sirt1 during mouse embryonic stem cells differentiation and mouse embryonic fibroblasts reprogramming. We further found that the reprogramming efficiency was reduced by the overexpression of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Notably, early SPD intervention slowed down the process significantly. Moreover, oxidative stress induces DNA damage and telomere dysfunction is an important mechanism of cell senescence [59][60][61][62][63][64]. Herein, visualized γ-H2AX immunofluorescence staining was performed to detect the DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, early SPD intervention slowed down the process significantly. Moreover, oxidative stress induces DNA damage and telomere dysfunction is an important mechanism of cell senescence [59][60][61][62][63][64]. Herein, visualized γ-H2AX immunofluorescence staining was performed to detect the DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Among the sirtuin members, SIRT1 is the most widely studied molecule. It is detected in the nucleus and involved in many cellular events including transcriptional silencing, DNA damage repair, cell cycle regulation, insulin regulation and longevity [56][57][58][59][60]. As a histone deacetylase, SIRT1 is recruited to the chromatin and deacetylates histone 1 lysine 26 (H1K26), H3K9, H3K14 and H4K16 [61].…”
Section: Sirt1mentioning
confidence: 99%
“…In addition, SIRT1 also deacetylates a number of transcription factors, including P53, FOXO, p300 histone acetyltransferase and E2F transcription factor 1 (E2F1) [62]. We and others have demonstrated that SIRT1 is highly expressed in both mESCs and hESCs [56,57,63]. In the following section, we review the importance of SIRT1 in regulating cell cycle progression and DDR.…”
Section: Sirt1mentioning
confidence: 99%
See 1 more Smart Citation
“…In replicative senescence (RS), cells reach senescence through serial division, and are permanently arrested although metabolically active ( Hayflick and Moorhead, 1961 ). RS cells display telomere shortening ( Harley et al, 1990 ; Allsopp et al, 1995 ; Blackburn, 2001 ; Cawthon et al, 2003 ; Masutomi et al, 2003 ; Ben-Porath and Weinberg, 2004 ; Ogami et al, 2004 ; Davis and Kipling, 2005 ; Canela et al, 2007 ), with accumulation of DNA damage through an inability to repair it ( Chen et al, 2020 ), de-repression of p16 INK 4a loci ( Zindy et al, 1997 ; Chkhotua et al, 2003 ; Krishnamurthy et al, 2004 ; Ressler et al, 2006 ) and alterations in Rb/p13 or p53/p21 CIP 1 pathways, both inducing senescence in different ways ( Chen et al, 2020 ). Oxidative stress-induced premature senescence (SIPS) is elicited through external or internal metabolic oxidative agents, causing severe or irreparable DNA damage ( te Poele et al, 2002 ; d’Adda di Fagagna et al, 2003 ; Parrinello et al, 2003 ; Bartkova et al, 2006 ; Di Micco et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%